Refining methods for attributing health impacts to climate change: a heat-mortality case study in Zürich - Rupert F. Stuart-Smith; Ana M. Vicedo-Cabrera; Sihan Li; Friederike E.L. Otto; Kristine Belesova; Andy Haines; Luke J. Harrington; Jeremy J. Hess; Rashmi Venkatraman; Thom Wetzer; Alistair Woodward; Kristie L. Ebi (Climatic Change, 2025)
Heat-related deaths occur throughout the summer months, peak during heatwaves, and are affected by temperature and exposed populations’ sensitivities to meteorological conditions. Previous studies found that climate change is increasing heat-related mortality worldwide. We build on existing epidemiological methods to shed light on the adverse effects of climate change on human health. We address limitations in existing methods and apply refined approaches to assess heat mortality attributable to human-induced climate change in Zürich, Switzerland, over 50 years (1969–2018) including a case study of summer 2018. Our methodological refinements affect how counterfactual climate scenarios are derived, and facilitate accounting for changing vulnerability, and assessing impacts during and outside heatwaves. We find nearly 1,700 heat-related deaths attributable to human-induced climate change between 1969 and 2018. Declining vulnerability to heat avoided at least 700 heat-related deaths. The approach described here could be applied elsewhere to quantify the effect of climate change on other health outcomes.